Cranial sexual dimorphism in the Kinda baboon (Papio hamadryas kindae). Issue 4 (6th September 2017) - Singleton, Michelle; Seitelman, Brielle C.; Krecioch, Joseph R.; Frost, Stephen R.
Abstract: Objectives: The smallest extant member of genus Papio, the Kinda baboon exhibits low sexual dimorphism and a distinctive cranial shape. Ontogenetic scaling accounts for most cranial‐shape differences within Papio, but studies have shown that the Kinda follows a separate ontogenetic trajectory. If so, its cranial‐dimorphism pattern should differ from other subspecies. To evaluate this hypothesis, morphometric analysis was used to investigate cranial dimorphism in Papio . Materials and methods: Three‐dimensional landmarks were digitized on 434 adult crania representing six Papio subspecies. Size‐ and shape‐dimorphism magnitudes were quantified using centroid size and Procrustes distances. Patterns of sex‐ and size‐related variation were explored using MAN(C)OVA, multivariate regression, and form‐space PCA. Canine dimorphism was investigated using dental metrics. Results: Kinda size and shape dimorphism are significantly lower than in other Papio subspecies. The relative magnitude of Kinda shape dimorphism is similar to other southern baboons; Kinda canine dimorphism is unremarkable. MAN(C)OVA results support subspecies differences in cranial dimorphism and scaling. Allometric and dimorphism vectors differ significantly in some subspecies, and their vector‐angle matrices are strongly correlated. The Kinda's allometric vector angles are divergent. Form‐space PC3, summarizing size‐independent dimorphism, separates the Kinda from other subspecies. Discussion: The Kinda baboon exhibits significantly lower size and shape dimorphism than other baboons, but its relative dimorphism levels are unexceptional. The Kinda differs from other subspecies in patterns of allometry, size‐related shape dimorphism, and residual shape dimorphism. Kinda facial shape is "masculinized" relative to size, especially in females, suggesting female sexual selection contributed to the evolution of Kinda dimorphism.